Peran Fikih Indonesia dalam Modernisasi Hukum Islam (Perspektif Undang-Undang Nomor 1 Tahun 1974) - Muhamad Muslih (Nurani Hukum, 2019)
There are several views of thought that hinder the process of developing Islamic law, even they argue that Islamic law cannot be developed. Joseph Schacht (1955) argued that the purpose of Muhammad SAW was appointed as a Prophet not to create a new legal system, but to guide humans to be able to go to heaven. Muhammad Khalid Mas'ud (1955), Asaf Ali Asghar Fyzee (1955), and Yahya Harahap (2003) argue that the process of modernizing Islamic law cannot be done by everyone, because it requires certain skills to do it and there are limits to objects that cannot be modernized. Islamic law is not a law in the sense of modern law.This study aims to prove that Islamic law in Indonesia always develops according to the needs of the society. Hasbi Ash-Shiddieqy (1975) argue that Islamic law is an attempt by legal experts to apply the Sharia to the needs of the society. ‘Fikih Indonesia’ initiated by Hasbi Ash-Shiddieqy has an important role in the process of modernizing Islamic law in Indonesia.The research method used in this research is Descriptive Qualitative and research data sources are classified as Library Research. The approach used is a Socio-Legal and Normative Juridical Approach. Primary data sources are Hasbi Ash-Shiddieqy's books and Undang-undang No. 1 Tahun 1974. Secondary data sources used are all writings, journals, books, articles, and other sources that are relevant to the discussion.The results of this study that Islamic law in Indonesia always develops according to the needs of the society. In terms of history, the role of ‘Fikih Indonesia’ initiated by Hasbi Ash-Shiddieqy has a very important role in the process of modernizing Islamic law in Indonesia. Because ‘Fikih Indonesia’ became the idea of the Draft Undang-undang Nomor 1 Tahun 1974. So there are many similarities between Undang-undang No. 1 Tahun 1974 and ‘Fikih Indonesia’. Keywords: Islamic Law, Modernization, Fikih Indonesia